2018
DOI: 10.5937/hraish1801033o
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antioxidative action of the two N-acetylcystein containing products: Propomucil® and Fluimucil® in a group of smokers who have seasonal coughing problems

Abstract: Obradović et al., Comparison of the antioxidative action of the two N-acetylcystein containing products: Propomucil® and Fluimucil® ...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Obradovic et al, demonstrated significant antioxidant protection from NAC-P when compared with NAC. 12 In our study, potential confounding factors were limited as the two groups of patients (NAC and NAC-P) were not significantly different for variables: age, smoking status, cough status, expectoration, sputum appearance, sputum volume, microbiological sputum test, and CRP values. However, our study possessed several limitations.…”
Section: Questionnairementioning
confidence: 72%
See 1 more Smart Citation
“…Obradovic et al, demonstrated significant antioxidant protection from NAC-P when compared with NAC. 12 In our study, potential confounding factors were limited as the two groups of patients (NAC and NAC-P) were not significantly different for variables: age, smoking status, cough status, expectoration, sputum appearance, sputum volume, microbiological sputum test, and CRP values. However, our study possessed several limitations.…”
Section: Questionnairementioning
confidence: 72%
“…11 Two studies indicated the importance of NAC with Propolis (NAC-P) in antioxidant protection and respiratory symptom reduction in pediatric patients with adenoid hypertrophy. 12,13 Propolis possesses antibacterial, antiviral, and antifungal effects. Unsurprisingly it is widely used as a treatment for upper respiratory tract infections.…”
Section: Introductionmentioning
confidence: 99%